Relevance of Hadith History of Imam al-Tirmidhī No. 1230 in Claw Machine Games - Hikmatul Izzah (Taqriri: Journal of Al-Hadith Science Studies, 2026)
Claw machines have become a popular form of modern entertainment in various shopping centers. However, the game's mechanism, which relies on uncertainty, often raises questions regarding its legal status from the perspective of Islamic jurisprudence (fiqh) regarding transactions, particularly regarding the element of gharar (intransitiveness). This study aims to analyze transaction practices in claw machine games through the Ma'ānī al-Ḥadīth approach, focusing on the prohibition of gharar as stipulated in the hadith narrated by Muslim. This article discusses the concept of gharar from an Islamic legal perspective and its relevance to modern gaming practices such as claw machines. In transactions, gharar arises when the contract contains elements of speculation and uncertainty, contrary to the principle of exchange contracts that require clarity of object, price, and time. The Prophet's hadith prohibiting the sale of "fish in water" serves as the basis for affirming the prohibition of speculative transactions. This article examines the relevance of this prohibition to claw machines, where players pay for uncertain and often opaque prizes, thus resembling transactions containing gharar. The discussion covers various forms of gharar, such as gharar in the contract, the object of the transaction, the non-existence or non-deliverability of the goods, the uncertainty of the price, and the uncertainty of the time of delivery. Thus, this article asserts that the speculative and uncertain elements present in claw machines bear similarities to the practice of gharar, which is prohibited in Islam.